Izitimela zakoBulawayo : railways and African women’s search for a better life in the ‘city of kings’, circa 1920-1950 - Paleker, Gairoonisa (University of Pretoria, 2020)
Dissertation (MSocSci (History))--University of Pretoria, 2019.